It’s not just the heart: respiratory limitations to constant-load exercise in adult Fontan patients and potential implications for rehabilitation - Kyle G. P. J. M. Bolye; Patrick Schön; Fernando G. Beltrami; Matthias Greutmann; Christina M. Spengler (Current Issues in Sport Science, 2024)
Introduction